Comparative study of efficacy of drotaverine hydrochloride and valethamate bromide with control in first stage of labour - Dahal, P; Banerjee, B; Uprety, DK; Das, BP; Thakur, A; Agrawal, A (Health Renaissance, 2013)
Background: Labour is the most perilous journey a woman has to undertake. Painless and short labour is desired by every woman and is a constant aim for obstetrician. Objective: To analyze and compare the efficacy and safety of drotaverine and valethamate with control group on improving cervical dilatation and promoting progress of labour. Method: Three hundred demographically similar women, both primigravida and multigravida with a term pregnancy in established labour were randomly divided into three groups. One hundred women (group 1) were given injection valethamate intramuscularly,100 women (group 2) were given drotaverine and the rest 100 (group 3) were not given any drug. Comparative analysis was carried out as regards to duration of first stage of labour, mode of delivery, maternal side effects and fetal outcome. Results: The mean duration of active phase of labour in group 1, 2 and 3 was 254.29±96.621 min, 178.31±73.412 min and 346.31±123.351 min respectively. The duration of injection to end of first stage of labour in valethamate and Drotaverine group was 228.12±84.626min and 168.89±69.576min respectively (p value<0.0001). The duration of injection to delivery in Valethamate was 249.13± 88.321 min and in Drotaverine was 192.56±75.479min (p value<0.0001). There were no serious maternal and fetal adverse effects in any group but minor side effects were more common in valethamate group. Conclusion: The reduction of the duration of the first stage of labour was apparently more in drotaverine group as compared to valethamate and control group. Drotaverine was found to be safe with minimal or no adverse effect on the mother and the fetus. Health Renaissance, January-April 2013; Vol. 11 No.1; 38-42 DOI: http://dx.doi.org/10.3126/hren.v11i1.7600